Geospatial Technology and the Role of Location in Science - Scholten, Henk J.; Velde, Rob.; Manen, Niels. (GeoJournal Library, 2009)
Globalisation has not led to the death of geography. Intensified relations between communities in different parts of the world have only highlighted the need for understanding and managing phenomena on a variety of geographic scales. From global warming to credit crunch, and from epidemics to terrorism, causes and solutions are sought on local, regional, national as well as inter-continental levels. With the advent of Geospatial Technology, scholars, policymakers and entrepreneurs have valuable tools in hand to proceed. This book offers the first systematic account of the science behind this mental and technological revolution. Tracing the adoption and dissemination of Geospatial Technology in a range of disciplines, it examines the impact this technology has had, and is likely to have, on the explanation of spatial behaviour, phenomena and processes. At the same time, stressing innovative usage, it explores scientific contributions to technology advancement.